Symbolic and aesthetic fusion in Keraton Surakarta: colonial influence and Javanese cultural resistance through architectural design adaptation - Imam Santosa; I. Kadek Dwi Noorwatha (Cogent Arts & Humanities)
This study examines the impact of Dutch colonialism on Javanese culture in the 18th and 19th centuries, focusing on the adaptive processes at Keraton Surakarta, as a cultural and political epicenter. It investigates how colonial power reshaped political, economic, social, and cultural structures, and how these transformations are embodied in the palace’s architecture. Employing a historical-qualitative method through archival sources and literature analysis, the study reveals that despite colonial dominance Keraton Surakarta endured as a symbol of Javanese identity and traditional sovereignty. Economically, it engaged with the forced cultivation system while maintaining indigenous socio-cultural practices. Socially Javanese rituals and court traditions despite external pressures. Architecturally, the palace blended European and Javanese elements, reflecting not only adaptation but also a deliberate strategy of cultural negotiation and symbolic resistance. This hybridity was instrumental in asserting identity and resilience amidst foreign rule. The study underscores architecture’s role as a medium for cultural preservation and political expression demonstrating how built environments can serve both as artifacts of adaptation and as living symbols of heritage. These findings contribute to a deeper understanding of cultural resilience and the dynamic preservation of historical sites within colonial contexts.